Loss of Vhl alters trabecular bone loss during S. aureus osteomyelitis in a cell-specific manner - Ford, Caleb A.; Hurford, Ian M.; Fulbright, Laura E.; Curry, Jacob M.; Peek, Christopher T.; Spoonmore, Thomas J.; Cruz Victorio, Virginia; Johnson, Joshua R.; Peck, Sun H.; Cassat, James E. (Frontiers in Cellular and Infection Microbiology, 2022)
Osteomyelitis, or bone infection, is a major complication of accidental trauma or surgical procedures involving the musculoskeletal system. Staphylococcus aureus is the most frequently isolated pathogen in osteomyelitis and triggers significant bone loss. Hypoxia-inducible factor (HIF) signaling has been implicated in antibacterial immune responses as well as bone development and repair. In this study, the impact of bone cell HIF signaling on antibacterial responses and pathologic changes in bone architecture was explored using genetic models with knockout of either Hif1a or a negative regulator of HIF-1α, Vhl. Deletion of Hif1a in osteoblast-lineage cells via Osx-Cre (Hif1aΔOB) had no impact on bacterial clearance or pathologic changes in bone architecture in a model of post-traumatic osteomyelitis. Knockout of Vhl in osteoblast-lineage cells via Osx-Cre (VhlΔOB) caused expected increases in trabecular bone volume per total volume (BV/TV) at baseline and, intriguingly, did not exhibit an infection-mediated decline in trabecular BV/TV, unlike control mice. Despite this phenotype, bacterial burdens were not affected by loss of Vhl. In vitro studies demonstrated that transcriptional regulation of the osteoclastogenic cytokine receptor activator of NF-κB ligand (RANKL) and its inhibitor osteoprotegerin (OPG) is altered in osteoblast-lineage cells with knockout of Vhl. After observing no impact on bacterial clearance with osteoblast-lineage conditional knockouts, a LysM-Cre model was used to generate Hif1aΔMyeloid and VhlΔMyeloid mouse models to explore the impact of myeloid cell HIF signaling. In both Hif1aΔMyeloid and VhlΔMyeloid models, bacterial clearance was not impacted. Moreover, minimal impacts on bone architecture were observed. Thus, skeletal HIF signaling was not found to impact bacterial clearance in our mouse model of post-traumatic osteomyelitis, but Vhl deletion in the osteoblast lineage was found to limit infection-mediated trabecular bone loss, possibly via altered regulation of RANKL-OPG gene transcription.